'I will learn from it for as long as I live' – religious reading and functional literacy skills. Issue 2 (4th May 2021) - Moilanen, Mikko; Sommerseth, Hilde Leikny
ABSTRACT: Max Weber claims in his well-known book, The Protestant Ethic and the Spirit of Capitalism, that the emergence of capitalism had its roots in the Protestant work ethic. Becker and Woessmann's seminal 2009 paper finds that the more likely relationship between Protestantism and economic prosperity runs via literacy. They claim that Protestants unintendedly acquired literacy skills that functioned as human capital in the economic sphere by adhering Luther's call to learn to read the Bible on their own. In this paper, we investigate at individual level to what extent one by reading Holy scripts acquired functional literacy skills. By using unique individual-level data from nineteenth-century Protestant Norway, we are able to identify offsprings of families known to be intensive readers of religious texts. Our results indicate that the effect of religious reading on functional literacy was restricted: religious reading gave better skills to read easily understood texts, but did not give better skills to read more advanced texts. Our results give more nuances in our understanding of what role pre-modern Nordic religious reading played in economic progress in Lutheran Nordic countries.